Network Exposure in the Propagation of the COVID-19 Pandemic - Markus Epp; Marius Jäger (ZBW - Leibniz Information Centre for Economics, 2021)
This paper develops a parsimonious model of individual exposure and of public health policy that can be used to study the evolution of an epidemic and the optimal use of lockdown policies and other non-pharmaceutical interventions. At the heart of individual exposure choices are the trade-offs between private utility derived from exposure and the risks of infection. Agents' utilities from private exposure are amplified by network benefits from social and economic activities, which amplifies the infection externality and constitutes a role for coordination policies due to multiple equilibria. We find that lockdowns do not prevail endogenously in equilibrium and that containment policy can significantly enhance welfare. Unpopularity of such contact restrictions imply that policy might face time inconsistency problems.
Keywords: E52; E58; E61; E63; 330; Pandemics; Endogenous exposure; SIR-macro; Network effects; Externality; Time inconsistency